Effects of cross sections library parameters on the OECD/NEA Oskarshamn-2 benchmark solution. (November 2015) - Balestra, P.; Parisi, C.; Giannetti, F.; Caruso, G.
Highlights: A 3D NK–TH model was developed using RELAP5-3D© for studying BWR instability events. A cross section library was generated using the available CASMO format data. To evaluate reactor stability parameters a tool was developed and validated. The effect of some neutronic parameters on the reactor stability was investigated. The Oskarshamn-2 1999 event stability parameters were properly reproduced. Abstract: The OECD/NEA proposes a new international benchmark based on data collected during an instability transient occurred at the Oskarshamn-2 NPP. This benchmark is aimed at testing the coupled 3D Neutron Kinetic–Thermal Hydraulic (3D NK–TH) codes on challenging situations. The ENEA "Casaccia" Research Center, is participating to this benchmark, developing a computational model using the RELAP5-3D© code. The 3DNK model has been already developed from the cross sections dataset calculated by OKG, the Oskarshamn-2 licensee, through the CASMO lattice code. In order to use this neutron cross sections database in RELAP5-3D© a n -dimensional polynomials data fitting and base cross sections values calculations are required. An ad-hoc tool, named PROMETHEUS, has been developed for automatically generating RELAP5-3D©-compatible cross sections libraries. This tool allows at easily visualizing the complex structure of the neutronic datasets; moreover it is exploited for deriving different cross sections libraries needed to evaluate neutronic parameters effects on the reactor instability prediction. Thus, the effects of the fuel temperature and control rod histories, of the discontinuity factors (averaged/not averaged) and of the neutron poisons has been assessed. A ranking table has been produced, demonstrating the relevance of the not-averaged discontinuity factors and of the on-transient neutron poisons calculations for the correct prediction of the Oskarshamn-2 event.